2002
DOI: 10.1038/nm0602-582
|View full text |Cite
|
Sign up to set email alerts
|

Local synthesis of complement component C3 regulates acute renal transplant rejection

Abstract: Accumulating evidence suggests that innate immunity interacts with the adaptive immune system to identify potentially harmful antigens and eliminate them from the host. A central facet of innate immunity is complement, which for some time has been recognized as a contributor to inflammation in transplant rejection but without detailed analysis of its role in what is principally a T cell mediated process. Moreover, epithelial and vascular tissues at local sites of inflammation secrete complement components; how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
381
4
3

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 473 publications
(400 citation statements)
references
References 27 publications
12
381
4
3
Order By: Relevance
“…This suggested that the observed C3 staining on the tubules was specific but was not correlated with IRI. Most likely, tubular C3 staining reflected local C3 synthesis (27) or a low level of alternative pathway complement activation. Semiquantitative analysis revealed no significant differences between sham-operated WT and IRI-challenged WT or CD59 Ϫ/Ϫ mice in the intensity of tubular C3 staining (Table I).…”
Section: Resultsmentioning
confidence: 99%
“…This suggested that the observed C3 staining on the tubules was specific but was not correlated with IRI. Most likely, tubular C3 staining reflected local C3 synthesis (27) or a low level of alternative pathway complement activation. Semiquantitative analysis revealed no significant differences between sham-operated WT and IRI-challenged WT or CD59 Ϫ/Ϫ mice in the intensity of tubular C3 staining (Table I).…”
Section: Resultsmentioning
confidence: 99%
“…This control can be overwhelmed by specific activators of this pathway, increased concentrations of alternative pathway components (due to local synthesis (20) or the release of these proteins by infiltrating neutrophils (21)), or insufficient function of the complement regulatory proteins (Fig. 2).…”
Section: Continous Active Control Of Alternative Pathway Activation Imentioning
confidence: 99%
“…This may be particularly important to bronchial inflammation in acute and chronic rejection of lung allografts. In fact, local C3 production has been demonstrated to modulate the rejection of renal allografts (64).…”
Section: Figurementioning
confidence: 99%